Elsevier's integrated review genetics - Adkison, Linda R. (Philadelphia, Pennsylvania : Elsevier Saunders, 2012)
Effectively merge basic science and clinical skills with Elsevier's Integrated Review Genetics, by Linda R. Adkison, PhD. This concise, high-yield title in the popular Integrated Review Series focuses on the core knowledge in genetics while linking that information to related concepts from other basic science disciplines. Case-based questions at the end of each chapter enable you to gauge your mastery of the material, and a color-coded format allows you to quickly find the specific guidance you need. Online access via www.studentconsult.com - included with your purchase - allows you to conveniently access the book's complete text and illustrations online as well as relevant content from other Student Consult titles. This concise and user-friendly reference provides crucial guidance for the early years of medical training and USMLE preparation.
Basic mechanisms -- Chromosomes in the cell -- Mechanisms of inheritance -- Genetics of metabolic disorders -- Cancer genetics -- Hematologic genetics and disorders -- Musculoskeletal disorders -- Neurologic diseases -- Cardiopulmonary disorders -- Hepatic, renal, and gastrointestinal systems -- Disorders of sexual differentiation and development -- Population genetics and medicine -- Modern molecular medicine.
Includes bibliographical references and index.
Keywords: MEDICAL GENETICS